20 Years of Legislation - How Australia Has Responded to the Challenge of Regulating Genetically Modified Organisms in the Clinic - O’Sullivan, Gabrielle M.; Philips, Joshua G.; Mitchell, Heidi J.; Dornbusch, Michael; Rasko, John E. J. (Frontiers in Medicine, 2022)
• In contrast to the prior voluntary system, since 2001, gene technology in Australia has been regulated under a legislated national Gene Technology Regulatory Scheme which is administered by the Gene Technology Regulator • The Scheme provides science-based assessment of the potential risks of gene technology to the health and safety of people and the environment • It complements the role of the Australian Therapeutic Goods Administration which regulates all therapeutic products in Australia to ensure they are safe and effective • Recent reforms to the Scheme contribute to, and anticipate, the continued safe development and delivery of gene-based human therapeutics in Australia while serving as a successful model for other jurisdictions